Television consumption and the construction of hybrid identity among female Javanese descendants in Malaysia / Lily El Ferawati Rofil - Lily El Ferawati, Rofil (2016)
The main purpose of this study was to explore television consumption and the construction of hybrid identity among female Javanese descendants in Malaysia. This study began with the enquiries about how Malay women of Javanese descent interpret their ethnicity and how television texts influence their interpretation of Javanese-Malay identity. The Javanese descendants who have been granted Malaysian citizenship are considered as Malays, even though in Indonesia, Javanese and Malay are two distinct ethnic groups. They have pleasantly enjoyed the status and the privileges of the Malays while maintaining some semblance of Javanese customs and traditions. As members of audience, they are exposed to representative images of Indonesia—the origin of Javanese—in foreign news and imported Indonesian soap operas, and at the same time they also experience narratives of subjectivity through local television content. With the presence of these local and transnational images of identity, along with their persistence of retaining cultural connections to Javanese imagined communities, the Javanese descendants are in practice compliant with two contexts of identity construction. This qualitative study employed audience ethnography as the methodology in which the data were collected through one-on-one interviews and participant observation in the field. The fieldwork was conducted in Kampung Parit Tujuh Baroh in Selangor district of Sabak Bernam, involving twenty respondents. The findings revealed that television played a substantial role in providing discourses of identity for the Malay-Javanese women to derive the definition of preferred and guided identities. The notion of preferred and guided identities, which constituted the concept of interpretive identity practices, explained how the Malay-Javanese women expressed their sense of belonging to multiple cultural identities. Their understanding of cultural, religious, and political discourses in television dramas, realities, and news illustrated their identifications with Javanese diaspora and Malay society. On the one hand, the findings describing the hybrid cultural life of the community under study could serve as an academic contribution to the field of ethnic and racial studies in the South East Asian region. On the other hand, the findings pertaining to audience interpretation of television and the concept of interpretive identity practices would contribute to the body of knowledge in media and cultural studies.